2020
DOI: 10.5530/pj.2020.12.97
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Genus Saurauia: Chemical Compounds and their Biological Activity

Abstract: Introduction: Saurauia plant has been widely used to treat a variety of diseases suffered by villagers at various places in the world. These species are widely used traditionally by the community as antidiabetic and digestive problems' remedy. This paper will present various uses and researches ever carried out by researchers in the world on various types of the genus Saurauia. Methods: The Information was collected from scientific journals, books, and reports. Results: This review summarizes the existing info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Saurauia bracteosa (Fruits) is used as a drug to treat diabetes, tumors, and cancer. This finding has also been further investigated by Pasaribu et al (2020), that Saurauia bracteosa have biological activity including antioxidant, cholesterol-lowering, antidiabetic, antihyperlipidemic, analgesic, antimicrobial, woundhealing, and immunostimulatory activity. Cocos nucifera (Fruits), a traditional food ingredient, has also been used in traditional medicine.…”
Section: Biological Ingredients Used In Harementioning
confidence: 84%
See 1 more Smart Citation
“…Saurauia bracteosa (Fruits) is used as a drug to treat diabetes, tumors, and cancer. This finding has also been further investigated by Pasaribu et al (2020), that Saurauia bracteosa have biological activity including antioxidant, cholesterol-lowering, antidiabetic, antihyperlipidemic, analgesic, antimicrobial, woundhealing, and immunostimulatory activity. Cocos nucifera (Fruits), a traditional food ingredient, has also been used in traditional medicine.…”
Section: Biological Ingredients Used In Harementioning
confidence: 84%
“…Furthermore, rice is used as a traditional medicine to treat inflammation, gastrointestinal ailments, hypercholesterolemia, diabetes, and skin diseases (Burlando and Comara 2014). In addition, Chrysophyllum roxburghii (Fruits) is reported to exert benefits as a uterine booster or fertilizer in women (Prashith et al 2014).…”
Section: Cultivated Plants 50%mentioning
confidence: 99%
“…Plants of Saurauia genus are widely distributed in Indonesia. One species that is considered quite widely known is Saurauia bracteosa which grows widely in the area of Lake Toba, North Sumatra, Indonesia [29]. Furthermore, Silalahi [30] reported that the leaves of Saurauia vulcanii were used for treating diarrhea, indigestion, and ethnomedicine for the Simalungun Batak sub-ethnic, in North Sumatra Province, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of Saurauia have long been used to treat a wide range of ailments worldwide by the indigenous communities (Pasaribu et al 2020), which includes digestive problems (Silalahi et al 2015), asthma, boils, bronchitis, depression of the central nervous system, fever, hepatitis B, piles, rheumatism, skin problems, seizure disorders, and ulcers (Uddin and Rahman 2006; Ahmed et al 2013). In the Philippines, the fruit of S. bontocensis is edible and used as raw materials for the food processing center that was built for enhancing livelihood opportunities for the Ikalahan Indigenous Peoples (Rice 2002).…”
Section: Introductionmentioning
confidence: 99%